Accounting Education in Latin America: Between Uniformity and Diversity - Armijos, Juan Carlos (2025)
This research identifies the differentiating aspects in the construction of program names and curricular approaches in accounting programs across Latin America, based on 345 programs from 325 universities in countries such as Argentina, Bolivia, Chile, Colombia, and Venezuela. The mixed methodology combines both qualitative and quantitative analysis. Fifty program names were identified, ranging from general titles like “Public Accountant” to specializations such as “Accounting and Auditing” or “Accounting and Finance.” The average duration of the programs is 9.1 semesters, with a range of 8 to 12 semesters. The analysis of curricula reveals considerable heterogeneity across countries and institutions, with significant variation in the areas of knowledge taught. Results from machine learning analysis indicate that the graduate profiles promised by universities often differ from those reflected in the curricular plans, suggesting a disconnect between the stated educational goals and the implemented study plans.